Community knowledge and practices as regards malaria in Ilorin city: implications for the elimination plan of the national malaria elimination program (2014)
Objective: To examine malaria-related knowledge and practices among residents in Ilorin City to guide forthcoming malaria elimination action of the recently restructured Nigerian National Malaria Elimination Program. Methods: Community-wide-cross-sectional study was conducted in June 2012 using pretested structured questionnaire and interview schedule to collect information on perception, prevention and treatment of malaria among the residents. Results: Majority of the respondents attributed malaria to mosquito bites and prevented the disease through multiple means including the use of long-lasting insecticide nets (60%), insecticide spray (54%) and mosquito coils (48%) alternatively. All the respondents spraying insecticides in the bedroom shortly before bed time stayed outdoors during night hours. Fifty three percent of the respondents treated the last malaria episode at the hospital/clinic, and the remaining (47%) employed self-medication. Only 6.1% of those who engaged in self-medication used artemisinin combination therapy drugs. Conclusions: Combined use of log-lasting insecticidal nets and insecticidal sprays call for investigation of behavioural and physiological insecticide resistance in the mosquitoes present in this area. Night time outdoor staying behavior mandated by spraying of insecticides and possible switch of the vectors to bite outdoor at early night hour also necessitate incorporation of outdoor mosquito control into the malaria elimination plan for this locality. Likewise, observation of self-medication in spite of high literacy levels implies that campaigns against such practice may not yield the desired result unless quality healthcare service is made affordable and accessible to all.